Β-Cyclodextrin Modified With Magnetic Nanoparticles Noncovalently for β-Naphthol Removal From Wastewater. Issue 1 (2nd January 2016) - Song, Xiao-Jie; Qin, Zhong-Qiong; Wang, Xian-Biao; Yang, Fan; Fang, Qun-Ling; She, Chen-Guang
Abstract : Magnetic cyclodextrin nanocomposites (β-CD-Fe3 O4 ) were prepared with magnetic nanoparticles (Fe3 O4 ) and β-cyelodextrin (β-CD) via the simple co-precipitation method. The product was characterized by X-ray diffraction (XRD), Thermogravity analysis (TGA) and scanning electron microscopy (SEM). UV-vis spectra and fluorescence spectra proved that the β-CD-Fe3 O4 could form host-guest inclusion complexes with β-naphthol (β-NOH), so β-CD-Fe3 O4 nanocomposites could detect and remove β-NOH from wastewater as a spectral probe. Furthermore, as a magnetic material, the β-CD-Fe3 O4 nanocomposites could be separated easily from aqueous solution by an external magnet, collected, and used circularly.